Peer Networks and Entrepreneurship: A Pan-African RCT - Fernando Vega-Redondo; Paolo Pin; Diego Ubfal; Cristiana Benedetti-Fasil; Charles Brummitt; Gaia Rubera; Dirk Hovy; Tommaso Fornaciari (Institute of Labor Economics (IZA), 2019)
Can large-scale peer interaction foster entrepreneurship and innovation? We conducted an RCT involving almost 5,000 entrepreneurs from 49 African countries. All were enrolled in an online business course, and the treatment involved random assignment to either face-to-face or virtual (Internet-mediated) interaction. We find positive treatment effects on both the submission of business plans and their quality, provided interaction displays some intermediate diversity. Network effects are also significant on both outcomes, although diversity plays a different role for each. This shows that effective peer interaction can be feasibly implemented quite broadly but must also be designed carefully, in view of the pursued objectives.
Keywords: C93; D04; D85; O12; O31; O35; 330; social networks; peer effects; entrepreneurship; innovation; semantic analysis